2020
DOI: 10.1159/000510083
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis Is Regulated by Mitochondria in Neurodegenerative Diseases

Abstract: <b><i>Background:</i></b> Neurodegenerative diseases are characterized by a gradual decline in motor and/or cognitive function caused by the selective degeneration and loss of neurons in the central nervous system, but their pathological mechanism is still unclear. Previous research has revealed that many forms of cell death, such as apoptosis and necrosis, occur in neurodegenerative diseases. Research in recent years has noticed that there is a new type of cell death in neurodegenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 157 publications
(228 reference statements)
2
30
0
Order By: Relevance
“…Several salient and established features of neurodegenerative diseases (e.g., lipid peroxidation and iron dyshomeostasis) are consistent with ferroptosis [87]. Ferroptosis is defined by Nomenclature Committee on Cell Death as "regulated cell death (RCD) initiated by oxidative perturbations of the intracellular microenvironment that is under constitutive control by Glutathione Peroxidase 4 (GPX4) and can be inhibited by iron chelators and lipophilic antioxidants" [88].…”
Section: Mechanisms Of Neurodegenerative Diseasementioning
confidence: 99%
“…Several salient and established features of neurodegenerative diseases (e.g., lipid peroxidation and iron dyshomeostasis) are consistent with ferroptosis [87]. Ferroptosis is defined by Nomenclature Committee on Cell Death as "regulated cell death (RCD) initiated by oxidative perturbations of the intracellular microenvironment that is under constitutive control by Glutathione Peroxidase 4 (GPX4) and can be inhibited by iron chelators and lipophilic antioxidants" [88].…”
Section: Mechanisms Of Neurodegenerative Diseasementioning
confidence: 99%
“…All neurodegenerative diseases are characterized by the progressive and irreversible loss of neurons from specific regions of the central and peripheral nervous systems, followed by a decline in neuronal, motor, and/or cognitive functions [ 107 ]. It was shown that cellular death driven by increased levels of iron, ROS, and consequent lipid peroxidation—ferroptosis—is an important contributor to neural cell death in Alzheimer's, Parkinson's, and Huntington's diseases, multiple sclerosis, and acute brain injury caused by cerebral ischemia, haemorrhagic insults, or brain trauma [ 108 111 ]. In addition, more recent studies have suggested that mitochondrial damage might be the ultimate step in ferroptosis-related oxidative cell death in neurodegeneration [ 112 ].…”
Section: Mitochondria and Ferroptosis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Although the detailed mechanism by which iron overload promotes ferroptosis has yet to determined, it is reasonable to hypothesize that iron overload may drive the generation of hydroxyl radicals, which further react with liposomes to produce lipid peroxidation products and cause mitochondrial dysfunction, and eventually ferroptosis [ 310 , 311 , 312 ]. Although mitochondria have been shown to be vital regulators of iron homeostasis and ferroptosis in neurodegenerative diseases [ 313 ], more direct evidence targeting iron overload, mitochondrial dysfunction, and ferroptosis is still required. The mitochondria are also the site for the synthesis of iron–sulfur cluster biogenesis (ISCs) and heme prosthetic groups.…”
Section: Molecular Mechanisms Of Metal-induced Mitochondrial Dysfunctionmentioning
confidence: 99%